Distribución de pollo campesino artesanal a domicilio por medio de plataformas digitales en Palmira. (2021)
The present work sought to know the viability of a business plan based on the commercialization of organic free-range chicken, processed in an artisanal way, the different digital platforms provided by the internet (social networks, email, e-commerce, web pages, etc.) to carry out commercial activity.